2019
DOI: 10.1016/j.wem.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

An Occupational Health Survey of British Mountain Guides Operating Internationally

Abstract: Introduction-Professional mountain guides face significant occupational health risks, including injuries, accidents, environmental exposures, chronic musculoskeletal strain, and psychological stressors. This study aims to investigate these risks and their impact on the quality of life of a group of international British mountain guides. Methods-This self-reported online survey included demographics; acute and chronic occupational conditions; and questions on general health, lifestyle, symptoms of post-traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Collectively, evidence from longitudinal studies on changes in overall mental health during expeditions appeared somewhat equivocal, but offer tentative evidence that some mental health symptoms might be more adversely affected during expeditions than others. The final code, post-traumatic stress disorder (PTSD), was mainly synthesised from crosssectional studies in mountain guides, who reported low levels of PTSD (Harkensee & Hillebrandt, 2019;Sommer et al, 2004).…”
Section: Cognitive Phenomena the Synthesis Generated Insights Into Perceived Cognitivementioning
confidence: 99%
“…Collectively, evidence from longitudinal studies on changes in overall mental health during expeditions appeared somewhat equivocal, but offer tentative evidence that some mental health symptoms might be more adversely affected during expeditions than others. The final code, post-traumatic stress disorder (PTSD), was mainly synthesised from crosssectional studies in mountain guides, who reported low levels of PTSD (Harkensee & Hillebrandt, 2019;Sommer et al, 2004).…”
Section: Cognitive Phenomena the Synthesis Generated Insights Into Perceived Cognitivementioning
confidence: 99%
“…Half of all dog walking injuries involve the upper extremity 9 . Hoverboard, skateboard, and mountain biking injuries often involve the upper extremity 10,11 , and most professional mountain guides report a hand or wrist injury at some point in their careers 12 .…”
mentioning
confidence: 99%